Turkey's Interest in Closer Relations with Russia: Global, Regional and Domestic Dynamics - (:unkn) unknown (ISTANBUL UNIV, 2020)
Recently, debates on a shift of axis in Turkish foreign policy have resurfaced. Many analysts perceive the geopolitical alignment between Turkey and Russia as a deliberate Turkish response to its deteriorating ties with the West. The goal of this paper is to shed light on the factors that have fostered the interest of the Turkish political elite in developing strategic relations with Russia. We argue that Turkey's alignment with Russia has global, regional and domestic dimensions. First, especially after the global financial crisis of 2008, Russia managed to successfully realign itself with rising powers like China and India, while also strengthening its traditional position as a global player. Second, in addition to its strong influence in the Black Sea, the Caucasus and Central Asia, Russia has become a major actor in other regions in the immediate neighborhood of Turkey such as the Middle East and the East Mediterranean. Finally, the failed coup attempt of July 2016 in Turkey has added a strong psychological dimension to the Turkish-Russian rapprochement. Nevertheless, Turkey's interest in closer ties with Russia is not expected to lead to a reorientation in Turkish foreign policy away from its position in the traditional transatlantic alliance.
Keywords: Turkey; Russia; Foreign Policy; Alignment; Syria; POLICY; COOPERATION; ORDER; WAR